The Determiners of Foreign Direct Investments: Case of Central Asian Republics - (:unkn) unknown (My University, 2020)
Foreign Direct Investment (FDI) is of vital importance especially in the economic developmentefforts of developing countries and constitutes the necessary capital resource for investments in the relevantcountries. The main reason why the former Eastern bloc countries, also called transition economies,experience economic growth and development problems after transition to the market system is the lack ofcapital accumulation in these economies. Also, in these countries, lower savings and higher consumptiontendencies emerge as another problem. Investments are also insufficient due to the low level of savings inthese countries. This situation brings with it a vicious cycle of low growth and development rate due to lackof savings and of investment. With the dissolution of the Union of Soviet Socialist Republics in the early1990s, the states that gained their independence faced socio-economic problems caused by a suddentransition from the centrally planned economy to the market economy. These economies, in which thetransition to the market system is quite painful, are therefore commonly referred to as "TransitionEconomies".Central Asian Turkish Republics, which are among the transition economies, also need externalfinancial resources to overcome problems such as lack of capital accumulation, low exchange income andpublic finance deficits. In this study, the factors that determine FDI in four Central Asian Republics(Kazakhstan, Turkmenistan and Kyrgyzstan, Uzbekistan) in the period between 2000 and 2016 wereanalyzed. For this purpose, variables such as economic growth, market size, macroeconomic stability, realeffective exchange rate and infrastructure development were used. For this purpose, the factors expected toaffect FDI were determined by using Dynamic Panel Data Analysis method by using the GMM estimator ofArellano-Bond (1991). As a result of the empirical analysis, an opposite relationship was found between thereal effective exchange rate (rer) and infrastructure (TEL) variables and the dependent variable. It is observedthat there is a similar relationship between macroeconomic stability, market size and economic growthvariables and dependent variable. The real effective exchange rate (rer), macroeconomic stability (inf) andinfrastructure (TEL) variables are statistically significant and largely explain the dependent variable.

Doğrudan Yabancı Yatırımlar (DYY), özellikle gelişmekte olan ülkelerin ekonomik kalkınma_x000D_ çabalarında hayati bir öneme sahip olmakta ve ilgili ülkelerde yatırımlar için gerekli sermaye kaynağını_x000D_ oluşturmaktadır. Geçiş ekonomisi olarak da adlandırılan eski Doğu bloku ülkelerinin piyasa sistemine_x000D_ geçtikten sonra ekonomik büyüme ve kalkınma sorunları yaşamalarının başlıca nedeni de bu ekonomilerde_x000D_ sermaye birikiminin yetersiz olmasıdır. Ayrıca bu ülkelerde tasarruf eğiliminin düşük; tüketim eğiliminin_x000D_ yüksek oluşu da diğer bir sorun olarak ortaya çıkmaktadır. İlgili ülkelerde tasarrufların düşük seviyede_x000D_ gerçekleşmesine bağlı olarak yatırımlar da yetersiz kalmakta; bu durum tasarruf ve yatırım eksikliğine bağlı_x000D_ olarak düşük büyüme ve kalkınma hızı şeklinde bir kısır döngüyü beraberinde getirmektedir. 1990’lı yılların_x000D_ başında Sovyet Sosyalist Cumhuriyetler Birliği’nin dağılmasıyla birlikte bağımsızlığını kazanan devletler,_x000D_ merkezi planlı ekonomiden piyasa ekonomisine ani bir geçişin yol açtığı sosyo-ekonomik sorunlarla_x000D_ karşılaşmışlardır. Piyasa sistemine geçişin oldukça sancılı bir biçimde gerçekleştiği söz konusu ekonomiler_x000D_ bu nedenle ‘’Geçiş Ekonomileri’’ olarak yaygın bir biçimde adlandırılmaktadırlar. Adı geçen geçiş_x000D_ ekonomilerinden olan Orta Asya Türk Cumhuriyetleri de sermaye birikimi yetersizliği, döviz gelirlerinin_x000D_ azlığı ve kamu finansman açıkları gibi sorunları aşabilmek için dışarıdan finansal kaynağa ihtiyaç_x000D_ duymaktadırlar. Bu bağlamda mevcut çalışmada, dört Orta Asya Cumhuriyetinde (Kazakistan, Türkmenistan_x000D_ ve Kırgızistan, Özbekistan) 2000-2016 yılları arasındaki dönemde DYY’ları belirleyen faktörler analiz_x000D_ edilmeye çalışılmıştır. Bu amaçla ekonomik büyüme, pazar büyüklüğü, makroekonomik istikrar, reel efektif_x000D_ döviz kuru ve altyapı gelişmişliği gibi değişkenlerden yararlanılmıştır. Bu amaçla DYY’lara etki etmesi_x000D_ beklenen faktörler Dinamik Panel Veri Analizi yöntemi ile Arellano-Bond (1991)’un GMM tahmincisi_x000D_ kullanılarak belirlenmeye çalışılmıştır. Yapılan ampirik analiz neticesinde, reel efektif döviz kuru (rer) ve_x000D_ altyapı (TEL) değişkenleri ile bağımlı değişken arasında zıt yönlü; makro ekonomik istikrar, pazar büyüklüğü_x000D_ ve ekonomik büyüme değişkenleri ile bağımlı değişken arasında aynı yönlü bir ilişki bulunduğu görülmüştür._x000D_ Reel efektif döviz kuru (rer), makroekonomik istikrar (inf) ve altyapı (TEL) değişkenleri, istatistiksel olarak_x000D_ anlamlı olup, bağımlı değişkeni büyük oranda açıklamaktadır
Doğrudan Yabancı Sermaye Yatırımlarının Belirleyicileri: Orta Asya Türk Cumhuriyetleri Örneği